Imaging of the major salivary glands. (16th October 2014) - Afzelius, Pia; Nielsen, Ming‐Yuan; Ewertsen, Caroline; Bloch, Klaus Poulsen
Summary: The major salivary glands, submandibular, parotid and sublingual glands play an important role in preserving the oral cavity and dental health. Patients with problems of the major salivary glands may present with symptoms such as dry mouth, dysphagia and obstruction of duct, inflammation, severe dental caries or swelling. Imaging plays an important role in visualization of morphology and function, to establish a diagnosis, for treatment, and for surgical planning. There are several options for diagnostic imaging: plain radiography, sialography, ultrasound (US), magnetic resonance imaging (MRI), computed tomography (CT), salivary gland scintigraphy and 18 F‐FDG positron emission tomography (PET). We present an overview of the modalities in relation to common salivary gland disease.